Barriers and facilitators to adherence to walking group exercise in older people living with dementia in the community: a systematic review - Vseteckova, J; Dadova, K; Gracia, R; Ryan, G; Borgstrom, E; Abington, J; Gopinath, M; Pappas, Y (European review of aging and physical activity, 2020)
BACKGROUND & AIMS: Evidence suggests that targeted exercise is important for people living with dementia. The aim of this review was to collect and synthesize evidence on the known barriers and facilitators to adherence to walking group exercise of older people living with dementia in the community. METHODS: We have searched appropriate electronic databases between January 1990 until September 2019, in any language. Additionally, we searched trial registries (clinicaltrial.gov and WHO ICTRP) for ongoing studies. We included all study designs. Studies were excluded when participants were either healthy older people or people suffering from dementia but living in residential care. Narrative synthesis was used. FINDINGS: 10 papers met the inclusion criteria. The narrative analysis focused on barriers, facilitators, and adherence. All studies reported on barriers and facilitators. Barriers included: bio-medical reasons (including mental wellbeing and physical ability); relationship dynamics; and socio-economic reasons and environmental issues. Facilitators included: bio-medical benefits & benefits related to physical ability; staff, group relationship dynamics and social aspect of walking group; environmental issues and individual tailoring; and participants perceptions about the walks & the program. Most studies did not provide data about adherence or attendance; where reported, adherence ranged from 47 to 89%. CONCLUSIONS: This systematic review of literature has highlighted known barriers and facilitators to adherence to walking groups type of exercise for people living with dementia in community. Carers' willingness to engage, their circumstances, perspectives and previous experiences of exercise seem to play a key role in facilitating adherence but there is little research that explores these. Also, the design, location and organisation of walking groups facilitate adherence. This reflects the need for such activities to be part of a wider 'program of care', tailored to the needs of the individual, flexible and convenient. Knowledgeable and well-trained instructors or healthcare professionals are recommended as group exercise leaders.
Keywords: Dementia; Walking group exercise; Adherence; Barriers; Facilitators; Ageing